Оценка влияния параметров синтеза на размер магнитных микрочастиц Fe(0); Медицинский Вестник Башкортостана; Т. 14, № 1 - Власов С. С. Сергей Сергеевич; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович); Кривощеков С. В. Сергей Владимирович; Безверхняя Е. А. Екатерина Александровна; Свиридова Е. В. Елизавета Витальевна; Постников П. С. Павел Сергеевич; Белоусов М. В. Михаил Валерьевич (2019, 2019)
Заглавие с экрана